Flame-retardant sunshade foaming coating fabric and preparation method thereof

By preparing polyglutamic acid containing dopa and phosphonic acid side groups to form phosphorus-nitrogen-silicon synergistic flame retardant SiO2 aerogel particles, the problems of smoke, toxic gas generation and poor water resistance in existing flame retardant fabrics are solved, and the problem of poor smoke generation and toxic gases in existing flame retardant fabrics is achieved. It has efficient flame retardant effect and good washing resistance.

CN119265956APending Publication Date: 2025-01-07ZHEJIANG DEYI SHADING TECH CO LTD

Patent Information

Application Number
CN202411482209.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing flame-retardant and sun-shading foamed coating fabrics use halogen and phosphorus-nitrogen flame retardants that cause smoke, toxic gas generation and environmental health hazards. Phosphorus-nitrogen flame retardants are insufficient in flame retardant performance, thermal stability and water resistance. Poor sex problem.

Method used

Prepare polyglutamic acid containing dopa and phosphonic acid side groups to form phosphorus-nitrogen-silicon synergistic flame retardant SiO2 aerogel particles, and mix it with polyacrylate slurry, and apply it to the surface of the sunshade fabric to form flame retardant sunshade Foam coated fabric.

Benefits of technology

A good flame retardant effect was achieved. The fabric burning time and smoldering time were less than 2s, the damage length was less than 5cm, and the water-resistant performance was good. The flame retardant performance did not significantly decrease after 10 washes. The process was simple, the raw materials were few, and the environment was Harmless to the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005097711570000081
    Figure BDA0005097711570000081
Patent Text Reader

Abstract

The invention discloses a flame-retardant sunshade foaming coating fabric and a preparation method thereof, and belongs to the technical field of functional textile processing. The fabric is prepared according to the following steps: mixing polyglutamic acid, dopamine, an amino-containing phosphonic acid compound and carbodiimide hydrochloride, and carrying out condensation reaction to prepare polyglutamic acid containing dopa and phosphonic acid side groups; the preparation method comprises the following steps: adding SiO2 aerogel particles, dopamine and polyglutamic acid containing dopa and phosphonic acid side groups into an alkaline solution to obtain a reaction mixed solution, and reacting to obtain a phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion liquid; adding polyacrylate slurry and a kerosene thickener into the phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion liquid to prepare a coating finishing liquid, coating the surface of a sunshade fabric with the coating finishing liquid, and drying to obtain the flame-retardant sunshade foaming coating fabric. The afterflame time and the smoldering time of the obtained fabric are less than 2s, the damaged length is less than 5cm, the fabric has good washing resistance, and the flame retardant property of the fabric is not obviously reduced after the fabric is washed for 10 times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a flame-retardant sunshade foaming coating fabric and a preparation method thereof, belonging to the technical field of functional textile processing. Background Art

[0002] Sunshade foaming coated fabrics are widely used in curtains, awnings, etc. Sunshade foaming coated fabrics are coated on the surface of ordinary fabrics. Usually, sunshade agents such as titanium dioxide, carbon black or other coatings are added to the coating resin finishing liquid. After mechanical foaming, they are coated on the fabric surface multiple times to achieve a sunshade effect.

[0003] Sunshade foam coated fabrics have high flame retardant rating requirements. According to the standard GB50222-2017 "Code for Fire Protection Design of Building Interior Decoration", decorative materials are divided into four levels according to their combustion performance: Class A non-combustible; Class B1 flame retardant; Class B2 flammable; Class B3 flammable, and the standard GB / T 17591-2006 "Classification of Fire Performance of Indoor Decoration Materials and Components", curtains should at least reach the flame retardant level of B1, that is, flame retardant materials.

[0004] At present, halogen and phosphorus-nitrogen flame retardants are widely used in the processing of flame-retardant textiles. Among them, the most commonly used halogen flame retardants have incomparable high efficiency compared with other flame retardant series, but the polymers added to them will produce a lot of smoke, toxic gases and corrosive gases when burned, which will harm the environment and human health. Therefore, it is the development trend of the industry not to use halogen-containing flame retardants in the processing of flame-retardant sunshade foam coating fabrics.

[0005] However, phosphorus-nitrogen flame retardants also have some disadvantages, such as insufficient flame retardant properties, insufficient thermal stability, poor water resistance, poor migration resistance, etc. These disadvantages may affect their fastness. Therefore, it is not suitable to directly apply the existing phosphorus-nitrogen flame retardants to flame-retardant sunshade foam coated fabrics, which will have the disadvantages of poor flame retardant effect and poor water washing fastness.

[0006] In the prior art, there are also technologies that study phosphorus-nitrogen flame retardants, but there are more or less problems and areas for improvement. For example, CN 112663340 A discloses that a polymer of acrylic esters wrapped in maleic anhydride-modified acrylamide is obtained by reacting acrylamide, maleic anhydride, glycidyl methacrylate, etc. as basic raw materials, and then forming nano copper for deposition, and adding aminosilane to obtain a textile flame retardant. Although the final flame retardant effect seems to be good, the preparation steps and raw material usage are too complicated and are not conducive to industrial use. In addition, the patent is aimed at textiles, but the technical means provided are vague and cannot be guaranteed to be implemented.

[0007] CN 107629250 B discloses a method of using formaldehyde, acrylic acid amide and ammonia to react to form modified urotropine, which is then polymerized with an organosilicon monomer under the action of a catalyst, and the modified urotropine is wrapped and adsorbed, and then the expansion efficiency is improved under the action of sodium nitrite. During the expansion process, the organosilicon polymer forms a cross-linked three-dimensional body, and then polyglutamic acid and 10-chloro-9,10-dihydro-9-oxa-10-phosphaphenanthrene are mixed with it for physical wrapping, and the organosilicon polymer is grafted with polyglutamic acid under the action of a catalyst to obtain a flame retardant. The technical steps are complicated, the raw materials used are of many types, and there is no record of its application on fabrics, and the flame retardant performance and water washing fastness on fabrics are not determined. Summary of the invention

[0008] Technical issues

[0009] Existing flame-retardant sunshade foam coating fabrics generally use halogen and phosphorus-nitrogen flame retardants to provide flame retardant properties, but halogen flame retardants will produce a lot of smoke, toxic gases and corrosive gases when burning, which are harmful to the environment and human health, and existing phosphorus-nitrogen flame retardants have the disadvantages of insufficient flame retardant properties, insufficient thermal stability, poor water resistance, poor migration resistance, etc. Therefore, it is necessary to develop a new type of phosphorus-nitrogen flame retardant suitable for flame-retardant sunshade foam coating fabrics.

[0010] Technical content

[0011] The purpose of the present invention is to provide a flame retardant sunshade foam coating fabric and a preparation method thereof. First, polyglutamic acid containing dopa and phosphonic acid side groups is prepared, which has the acid source, carbon source and gas source structure of the phosphorus-nitrogen flame retardant. Then, the reactivity and adhesion of dopamine are utilized, and dopamine reacts with the dopa side groups in the modified polyglutamic acid, and at the same time adheres to the surface of SiO2 aerogel particles together. The polyglutamic acid containing dopa and phosphonic acid side groups and polydopamine are firmly combined on the surface of the SiO2 aerogel particles to form a SiO2 aerogel particle with a phosphorus-nitrogen-silicon synergistic flame retardant effect. The prepared modified SiO2 aerogel particles are mixed with polyacrylate slurry and coated on the surface of the sunshade fabric to obtain a flame retardant sunshade foam coating fabric.

[0012] In order to achieve the above object, the present invention provides a flame retardant sunshade foam coating fabric, and the flame retardant sunshade foam coating fabric is prepared according to the following steps:

[0013] (1) Preparation of polyglutamic acid containing DOPA and phosphonic acid side groups:

[0014] The mixed solution is prepared by mixing polyglutamic acid, dopamine, a phosphonic acid compound containing an amino group and carbodiimide hydrochloride, and the mixed solution is subjected to a condensation reaction to prepare polyglutamic acid containing dopamine and a phosphonic acid side group;

[0015] (2) Preparation of phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion:

[0016] Adding SiO2 aerogel particles, dopamine, and polyglutamic acid containing dopamine and phosphonic acid side groups into an alkaline solution to obtain a reaction mixture, and stirring the mixture to obtain a phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion;

[0017] (3) Preparation of flame-retardant gas gel particle sunshade foam coating fabric:

[0018] Add polyacrylate slurry and kerosene thickener to the phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion obtained in step (2), prepare a coating finishing liquid, apply it on the surface of the sunshade fabric, and obtain a flame-retardant sunshade foamed coating fabric after drying.

[0019] In one embodiment of the present invention, in step (1), the concentration of polyglutamic acid in the mixed solution is 5 to 50 g / L.

[0020] In one embodiment of the present invention, in step (1), the concentration of dopamine in the mixed solution is 1 to 10 g / L.

[0021] In one embodiment of the present invention, in step (1), the amino-containing phosphonic acid compound is selected from at least one of 4-amino-1-hydroxybutylene-1,1-diphosphonic acid (alendronic acid), 4-aminobutylphosphonic acid, 2-aminoethylphosphonic acid, 3-aminobutylphosphonic acid, and 3-aminopropylphosphonic acid.

[0022] In one embodiment of the present invention, in step (1), the concentration of the amino-containing phosphonic acid compound in the mixed solution is 1 to 10 g / L.

[0023] In one embodiment of the present invention, in step (1), the concentration of carbodiimide hydrochloride in the mixed solution is 0.5-4 g / L.

[0024] In one embodiment of the present invention, in step (1), the pH of the mixed solution is 5.5-6.5; the pH is adjusted using acetic acid and sodium acetate buffer.

[0025] In one embodiment of the present invention, in step (1), the solvent of the mixed solution is water.

[0026] In one embodiment of the present invention, in step (1), the condensation reaction is carried out at a temperature of 20 to 40° C. and a reaction time of 0.5 to 12 hours.

[0027] In one embodiment of the present invention, in step (2), the pH of the alkaline solution is 7.5-9.

[0028] In one embodiment of the present invention, in step (2), the alkaline solution is any one of phosphate buffer, Tris-hydrochloric acid buffer or sodium bicarbonate solution.

[0029] In one embodiment of the present invention, in step (2), the concentration of nano-SiO2 aerogel particles in the reaction mixture is 10-100 g / L.

[0030] In one embodiment of the present invention, in step (2), the concentration of DOPA and phosphonic acid side group polyglutamic acid in the reaction mixture is 5 to 20 g / L.

[0031] In one embodiment of the present invention, in step (2), the concentration of dopamine in the reaction mixture is 2-10 g / L.

[0032] In one embodiment of the present invention, in step (2), the stirring reaction is carried out at a temperature of 20 to 30° C. for a time of 1 to 6 hours.

[0033] In one embodiment of the present invention, in step (3), the mass fraction of the polyacrylate slurry in the coating finishing liquid is 15-30%.

[0034] In one embodiment of the present invention, in step (3), the mass fraction of the kerosene thickener in the coating finishing liquid is 2-3%.

[0035] In one embodiment of the present invention, in step (3), the flame retardant sunshade coating fabric is increased in weight by 20-30 g / m relative to the sunshade fabric. 2 .

[0036] In one embodiment of the present invention, in step (3), the drying temperature is 150-180° C. and the drying time is 2-5 min.

[0037] In one embodiment of the present invention, in step (3), the sunshade fabric is prepared by the following steps:

[0038] ① Prepare a black slurry for a foaming coating: take nano titanium dioxide particles, carbon black, polyacrylate slurry, ammonium stearate emulsion and water, mix them evenly to obtain a mixed black slurry, adjust the pH of the mixed slurry to 8-9, and obtain a black slurry for a foaming coating; in the mixed black slurry, the mass fraction of the polyacrylate slurry is 70%-85%, the mass fraction of the ammonium stearate emulsion is 2%-10%, the mass fraction of the nano titanium dioxide particles is 0.5%-1%, the mass fraction of the carbon black is 0.1%-0.5%, and the rest is water;

[0039] ②Preparing a white slurry for a foaming coating: taking polyacrylate slurry, titanium dioxide slurry, ammonium stearate emulsion and water, mixing them evenly to obtain a mixed white slurry, adjusting the pH of the mixed slurry to 8-9, and obtaining a white slurry for a foaming coating; in the mixed white slurry, the mass fraction of the polyacrylate slurry is 70%-80%, the mass fraction of the titanium dioxide slurry is 10%-15%, the mass fraction of the ammonium stearate emulsion is 5%-10%, and the mass fraction of water is 0-10%;

[0040] ③ Preparation of shading fabric: foam the slurries obtained in steps ① and ② respectively, with a foaming ratio of 1:3 to 1:4, and then apply the foamed slurries on the surface of the fabric in the order of white slurry, black slurry and white slurry. After each application, bake at 150 to 180° C. for 2 to 5 minutes to finally obtain shading fabric; the weight gain of shading fabric is in the range of 20 to 40 g / m 2 .

[0041] The present invention also provides an application of the flame-retardant sunshade foamed coating fabric in the field of flame-retardant fabrics or sunshade.

[0042] Beneficial effects of the present invention:

[0043] (1) In the present invention, a macromolecular flame retardant containing polyglutamic acid with DOPA and phosphonic acid side groups is first synthesized, and its molecular structure contains the acid source, carbon source and gas source structure required by the phosphorus-nitrogen flame retardant, which integrates the flame retardant effect that requires multiple compounds to work together, and helps to exert a synergistic flame retardant effect. At the same time, the macromolecular flame retardant containing polyglutamic acid with DOPA and phosphonic acid side groups contains a dopa structure. Under the reactivity and adhesion of dopamine, a firm polyglutamic acid / polydopamine modified layer containing dopa and phosphonic acid side groups can be formed on the surface of SiO2 aerogel particles, so that the SiO2 aerogel particles and the polyglutamic acid containing dopa and phosphonic acid side groups are tightly combined to obtain polyglutamic acid / polydopamine modified SiO2 aerogel particles containing dopa and phosphonic acid side groups. The product has a phosphorus-nitrogen-silicon synergistic flame retardant effect, good flame retardant effect, and the obtained fabric afterburning time and smoldering time are both less than 2s, and the damaged length is less than 5cm.

[0044] (2) The polyglutamic acid / polydopamine modified SiO2 aerogel particles containing dopa and phosphonic acid side groups contain a large number of reactive groups, such as amino, carboxyl, phenolic hydroxyl, etc., which enable them to undergo cross-linking reactions with reactive polyacrylic resins, thereby improving the fastness of the flame-retardant particles in the coating and giving the flame-retardant sunshade foam coating fabric good flame retardant durability. The flame-retardant sunshade foam coating fabric prepared by the method of the present invention therefore also has good water washing resistance. After washing 10 times, the flame retardant performance of the fabric did not show a significant decrease.

[0045] (3) The preparation process of polyglutamic acid / polydopamine modified SiO2 aerogel particles containing dopa and phosphonic acid side groups has mild conditions and simple steps. It can be prepared by only two steps of reaction. At the same time, a small number of raw materials are used, and only 5 raw materials are used. At the same time, the modified aerogel particles have no adverse effects on human health and the environment. After a fire or other accident occurs, the flame retardant will not produce toxic gases when burning. DETAILED DESCRIPTION

[0046] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0047] Test method:

[0048] Flame retardant performance: refer to GBT5455-2014 Textile combustion performance - Determination of vertical direction damage length, smoldering and afterflaming time, test according to condition B in the standard, and calculate the afterflaming time, smoldering time and damage length of the sample.

[0049] The raw materials used in the examples are:

[0050] Polyester fabric: pure polyester woven fabric, 95g / m 2 ;

[0051] Polyglutamic acid: food grade;

[0052] Alendronic acid: purity ≥98%;

[0053] 4-Aminobutylphosphonic acid: purity ≥95%;

[0054] Dopamine hydrochloride: purity 98%;

[0055] 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: purity 98%

[0056] Nano-SiO2 aerogel particles: Hebei Dayu Environmental Protection Technology Co., Ltd., pore size 20 μm, hydrophilic type;

[0057] Polyacrylate slurry: Allnex Resins (China) Co., Ltd., model Valbond 8020;

[0058] Kerosene thickener: Transfar Intelligent Technology Co., Ltd., model TF-313CT;

[0059] Ammonium stearate emulsion: Tongxiang Hongyuan Textile Auxiliary Factory, model DT-100830C, solid content 30%;

[0060] Unless otherwise specified, other raw materials are common commercially available materials.

[0061] Example 1

[0062] A method for preparing a flame-retardant sunshade foaming coating fabric comprises the following steps:

[0063] (1) Preparation of polyglutamic acid containing DOPA and phosphonic acid side groups: 0.1 M acetic acid and sodium acetate were used to prepare a buffer solution with a pH of 6. 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), alendronic acid, polyglutamic acid, and dopamine were added to the pH 6 buffer solution. The mixture was stirred and reacted at 40° C. for 5 hours. The final concentrations of the components in the solution were 1 g / L EDC, 3 g / L alendronic acid, 20 g / L polyglutamic acid, and 2 g / L dopamine. After the reaction, the mixture was freeze-dried to obtain polyglutamic acid containing DOPA and phosphonic acid side groups.

[0064] (2) Preparation of phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion: 0.1 M sodium dihydrogen phosphate and disodium hydrogen phosphate are used to prepare a buffer solution with a pH of 8. The polyglutamic acid containing dopa and phosphonic acid side groups prepared in step (1) is added to the buffer solution with a pH of 8 to a concentration of 10 g / L in the solution. Nano-SiO2 aerogel particles and dopamine are added to a concentration of 50 g / L and 5 g / L of nano-SiO2 aerogel particles and dopamine in the solution. The reaction is then stirred at room temperature for 3 hours. After the reaction is completed, a phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion is obtained.

[0065] (3) Preparation of flame-retardant gas gel particle sunshade foam coating fabric: Take the phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion prepared in step (2), add polyacrylate slurry and kerosene thickener thereto, and prepare a coating finishing liquid, wherein the mass fraction of polyacrylate slurry in the coating finishing liquid is 20%, the mass fraction of kerosene thickener is 2.5%, and the remainder is phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion; after stirring and thickening, apply the coating finishing liquid to the surface of the shading fabric, and bake at 150°C for 4 minutes to obtain a phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel shading coating fabric, which has a weight increase of 30g / m relative to the shading fabric. 2 .

[0066] The method for preparing the shading fabric used in step (3) comprises the following steps:

[0067] ① Prepare a black slurry for a foaming coating: weigh nano titanium dioxide particles, carbon black, polyacrylate slurry, ammonium stearate emulsion and water, mix them evenly to obtain a mixed black slurry, in which the mass fraction of polyacrylate slurry is 70%, the mass fraction of ammonium stearate emulsion is 4%, the mass fraction of nano titanium dioxide particles is 0.5%, the mass fraction of carbon black is 0.1%, and the balance is water; add a small amount of ammonia water to the mixed black slurry, adjust the pH of the slurry to 8-9, and obtain a black slurry for a foaming coating;

[0068] ②Prepare white slurry for foaming coating: weigh polyacrylate slurry, titanium dioxide slurry, ammonium stearate emulsion and water, mix them evenly to obtain a mixed white slurry, in which the mass fraction of polyacrylate slurry is 80%, the mass fraction of titanium dioxide slurry is 12%, the mass fraction of ammonium stearate emulsion is 5%, and the balance is water; add a small amount of ammonia water to the mixed white slurry, adjust the pH of the slurry to 8-9, and obtain a white slurry for foaming coating;

[0069] ③ The two slurries prepared above were foamed with an egg beater (foaming ratio 1:3), and three layers of white slurry, black slurry and white slurry were applied to the surface of the polyester fabric in the order of three layers. After each coating, the slurry was baked at 180°C for 2 minutes to obtain a light-shielding coated fabric. The weight gain of the fabric after baking after each coating was controlled to be 30 g / m 2 .

[0070] Example 2

[0071] A method for preparing a flame-retardant sunshade foaming coating fabric comprises the following steps:

[0072] (1) Preparation of polyglutamic acid containing DOPA and phosphonic acid side groups: 0.1 M acetic acid and sodium acetate were used to prepare a buffer solution with a pH of 5. 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC), alendronic acid, polyglutamic acid, and dopamine were added to the buffer solution with a pH of 5. The mixture was stirred and reacted at 35° C. for 3 hours. The final concentrations of the components in the solution were 2 g / L EDC, 3 g / L 4-aminobutylphosphonic acid, 30 g / L polyglutamic acid, and 3 g / L dopamine. After the reaction, the mixture was freeze-dried to obtain polyglutamic acid containing DOPA and phosphonic acid side groups.

[0073] (2) Preparation of phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion: 0.1 M sodium dihydrogen phosphate and disodium hydrogen phosphate are used to prepare a buffer solution with a pH of 8. The polyglutamic acid containing dopa and phosphonic acid side groups prepared in step (1) is added to the buffer solution with a pH of 8 to a concentration of 8 g / L in the solution. Nano-SiO2 aerogel particles and dopamine are added to a concentration of 40 g / L and 4 g / L of nano-SiO2 aerogel particles and dopamine in the solution. The reaction is then stirred at room temperature for 5 hours. After the reaction is completed, a phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion is obtained.

[0074] (3) Preparation of flame-retardant gas gel particle sunshade foam coating fabric: Take the phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion prepared in step (2), add polyacrylate slurry and kerosene thickener thereto, and prepare a coating finishing liquid, wherein the mass fraction of polyacrylate slurry in the coating finishing liquid is 25%, the mass fraction of kerosene thickener is 3%, and the balance is phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion; after stirring and thickening, apply the coating finishing liquid to the surface of the shading fabric, and bake at 180°C for 3 minutes to obtain a phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel shading coating fabric, which has a weight increase of 25g / m2 relative to the shading fabric. 2 .

[0075] The method for preparing the shading fabric used in step (3) comprises the following steps:

[0076] ① Prepare a black slurry for a foaming coating: weigh nano titanium dioxide particles, carbon black, polyacrylate slurry, ammonium stearate emulsion and water, mix them evenly to obtain a mixed black slurry, in which the mass fraction of the polyacrylate slurry is 80%, the mass fraction of the ammonium stearate emulsion is 6%, the mass fraction of the nano titanium dioxide particles is 0.8%, the mass fraction of the carbon black is 0.3%, and the balance is water; drop a small amount of ammonia water into the mixed black slurry, adjust the pH of the slurry to 9, and obtain a black slurry for a foaming coating;

[0077] ②Preparing white slurry for foaming coating: weighing polyacrylate slurry, titanium dioxide slurry, ammonium stearate emulsion and water, mixing them evenly to obtain a mixed white slurry, in which the mass fraction of polyacrylate slurry is 70%, the mass fraction of titanium dioxide slurry is 10%, the mass fraction of ammonium stearate emulsion is 10%, and the balance is water; adding a small amount of ammonia water to the mixed white slurry, adjusting the pH of the slurry to 8.5, and obtaining a white slurry for foaming coating;

[0078] ③ The two slurries prepared above were foamed with an egg beater (foaming ratio 1:4), and three layers of white slurry, black slurry and white slurry were applied to the surface of the polyester fabric in the order of three layers. After each coating, the slurry was baked at 150°C for 5 minutes to obtain a light-shielding coated fabric. The weight gain of the fabric after baking after each coating was controlled to be 35g / m 2 .

[0079] Comparative Example 1

[0080] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not include step (1) and step (2), and in step (3), the preparation method of the shading coated fabric is: weighing polyacrylate slurry, kerosene thickener and water to prepare a coating finishing liquid, wherein the mass fraction of the polyacrylate slurry in the coating finishing liquid is 25%, the mass fraction of the kerosene thickener is 3%, and the balance is water; after stirring and thickening, coating the shading fabric on the surface, drying to obtain the shading coated fabric, and controlling the coating fabric to increase in weight by 20 g / m2 relative to the shading fabric after drying. 2 .

[0081] The preparation method of the shading fabric in Comparative Example 1 comprises the following steps:

[0082] ① Prepare a black slurry for a foaming coating: weigh nano titanium dioxide particles, carbon black, polyacrylate slurry, ammonium stearate emulsion and water, mix them evenly to obtain a mixed black slurry, in which the mass fraction of the polyacrylate slurry is 75%, the mass fraction of the ammonium stearate emulsion is 4%, the mass fraction of the nano titanium dioxide particles is 0.6%, the mass fraction of the carbon black is 0.3%, and the balance is water; drop a small amount of ammonia water into the mixed black slurry, adjust the pH of the slurry to 9, and obtain a black slurry for a foaming coating;

[0083] ②Prepare white slurry for foaming coating: weigh polyacrylate slurry, titanium dioxide slurry, ammonium stearate emulsion and water, mix them evenly to obtain a mixed white slurry, in which the mass fraction of polyacrylate slurry is 75%, the mass fraction of titanium dioxide slurry is 15%, the mass fraction of ammonium stearate emulsion is 6%, and the balance is water; add a small amount of ammonia water to the mixed white slurry, adjust the pH of the slurry to 9, and obtain a white slurry for foaming coating;

[0084] ③ Use an egg beater to foam the slurry (foaming ratio 1:3.5), and apply three layers of white slurry, black slurry and white slurry on the surface of the polyester fabric in the order of white slurry, black slurry and white slurry. After each coating, bake at 160℃ for 3 minutes to obtain a light-shielding coated fabric. The weight gain of the fabric after baking after each coating is controlled to be 40g / m 2 .

[0085] Comparative Example 2: Omitting the amino-containing phosphonic acid compound

[0086] The difference between Comparative Example 2 and Example 1 is that alendronic acid is not added in step (1).

[0087] Comparative Example 3: Omitting Dopamine

[0088] The difference between Comparative Example 3 and Example 1 is that dopamine is not added in step (1).

[0089] Comparative Example 4: Omitting polyglutamic acid

[0090] The difference between Comparative Example 4 and Example 1 is that polyglutamic acid is not added in step (1).

[0091] Comparative Example 5: Omitting SiO2 aerogel particles

[0092] The difference between Comparative Example 5 and Example 1 is that no nano-SiO2 aerogel particles are added in step (2).

[0093] The flame retardant properties of the samples in the above-mentioned Examples 1 to 2 and Comparative Examples 1 to 5 were measured, including the afterflaming time, smoldering time and damaged length; the samples in Examples 1 to 2 and Comparative Examples 1 to 5 were washed with 1 g / L detergent LS at 60°C for 15 minutes, dried and then washed again, and the flame retardant properties of the samples were measured after washing 10 times. The data obtained are listed in Table 1.

[0094] Table 1 Flame retardant properties of different shading fabrics

[0095]

[0096] From Table 1, we can see that:

[0097] ① In Example 1 and Example 2, the flame retardant sunshade foam coating fabric samples prepared by the method of the present invention have good flame retardant properties, the afterflaming time and the smoldering time are both less than 2s, the damaged length is less than 4cm, and the flame retardant properties do not show a significant decrease after washing.

[0098] ② The conventional process is used to coat the polyester fabric. The afterflaming time (15.2s), smoldering time (23.2s) and damaged length (18.7cm) of the prepared shading coated fabric (Comparative Example 1) are much longer than those of the flame-retardant sunshade foam coated fabric prepared by the method of the present invention, indicating that the polyester sunshade fabric prepared by the conventional process has no flame retardant properties.

[0099] ③Comparative Example 2 omits the alendronic acid in Example 1 to obtain a nitrogen-silicon synergistic flame retardant SiO2 aerogel coating sunshade fabric without alendronic acid. It can be seen that the flame retardant performance of the sunshade coating fabric without alendronic acid is better than that of Comparative Example 1, but far worse than that of the example.

[0100] ④ Comparative Example 3 omits dopamine in step (1) of Example 1. It can be seen that the flame retardant performance of Comparative Example 3 is better than that of Comparative Example 1, but not as good as that of Example 1, indicating that the dopamine side groups in the polyglutamic acid containing dopamine and phosphonic acid side groups play a key role in the subsequent application of the flame retardant.

[0101] ⑤ Comparative Example 4 omits the polyglutamic acid in Example 1. It can be seen that the flame retardant properties of the fabric before and after washing without polyglutamic acid are worse than those of the example, indicating that the presence of polyglutamic acid improves the flame retardant effect of alendronic acid.

[0102] ⑥ In comparative example 5, the SiO2 aerogel particles in Example 1 are omitted. The fabric has a good flame retardant effect before washing, but it is still not as good as the embodiment. The flame retardant effect deteriorates after washing, indicating that the introduction of SiO2 aerogel particles can enhance the flame retardant effect and water washability of the entire system.

[0103] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A flame retardant sunshade foam coating fabric, characterized in that: The flame retardant sunshade foaming coating fabric is prepared according to the following steps: (1) Preparation of polyglutamic acid containing DOPA and phosphonic acid side groups: The mixed solution is prepared by mixing polyglutamic acid, dopamine, a phosphonic acid compound containing an amino group and carbodiimide hydrochloride, and the mixed solution is subjected to a condensation reaction to prepare polyglutamic acid containing dopamine and a phosphonic acid side group; In the mixed solution, the concentration of polyglutamic acid is 5-50 g / L, the concentration of dopamine is 1-10 g / L, the concentration of amino-containing phosphonic acid compounds is 1-10 g / L, and the concentration of carbodiimide hydrochloride is 0.5-4 g / L; (2) Preparation of phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion: Adding SiO2 aerogel particles, dopamine, and polyglutamic acid containing dopamine and phosphonic acid side groups into an alkaline solution to obtain a reaction mixture, and stirring the mixture to obtain a phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion; In the reaction mixture, the concentration of nano-SiO2 aerogel particles is 10-100 g / L, the concentration of polyglutamic acid containing DOPA and phosphonic acid side groups is 5-20 g / L, and the concentration of dopamine is 2-10 g / L; (3) Preparation of flame-retardant gas gel particle sunshade foam coating fabric: Add polyacrylate slurry and kerosene thickener to the phosphorus-nitrogen-silicon synergistic flame-retardant SiO2 aerogel particle dispersion obtained in step (2) to prepare a coating finishing liquid, in which the mass fraction of the polyacrylate slurry is 15-30%, and the mass fraction of the kerosene thickener is 2-3%, and apply it to the surface of the sunshade fabric, and obtain the flame-retardant sunshade foamed coating fabric after drying.

2. The flame retardant sunshade foaming coated fabric according to claim 1, characterized in that: In step (1), the amino group-containing phosphonic acid compound is selected from at least one of 4-amino-1-hydroxybutylene-1,1-diphosphonic acid (alendronic acid), 4-aminobutylphosphonic acid, 2-aminoethylphosphonic acid, 3-aminobutylphosphonic acid, and 3-aminopropylphosphonic acid.

3. The flame retardant sunshade foaming coated fabric according to claim 1, characterized in that: In step (1), the pH of the mixed solution is 5.5 to 6.

5.

4. The flame retardant sunshade foam coating fabric according to claim 1, characterized in that: In step (1), the conditions for the condensation reaction are a temperature of 20 to 40° C. and a reaction time of 0.5 to 12 hours.

5. The flame retardant sunshade foaming coated fabric according to claim 1, characterized in that: In step (2), the pH of the alkaline solution is 7.5-9.

6. The flame retardant sunshade foaming coated fabric according to claim 1, characterized in that: In step (2), the alkaline solution is any one of phosphate buffer, Tris-hydrochloric acid buffer or sodium bicarbonate solution.

7. The flame retardant sunshade foaming coated fabric according to claim 1, characterized in that: In step (2), the stirring reaction is carried out at a temperature of 20 to 30° C. and for a time of 1 to 6 hours.

8. The flame retardant sunshade foaming coated fabric according to claim 1, characterized in that: In step (3), the flame retardant sunshade coating fabric is increased in weight by 20-30 g / m2 relative to the sunshade fabric. 2 .

9. The flame retardant sunshade foam coating fabric according to claim 1, characterized in that: In step (3), the sunshade fabric is prepared by the following steps: ① Prepare a black slurry for a foaming coating: take nano titanium dioxide particles, carbon black, polyacrylate slurry, ammonium stearate emulsion and water, mix them evenly to obtain a mixed black slurry, adjust the pH of the mixed slurry to 8-9, and obtain a black slurry for a foaming coating; in the mixed black slurry, the mass fraction of the polyacrylate slurry is 70%-85%, the mass fraction of the ammonium stearate emulsion is 2%-10%, the mass fraction of the nano titanium dioxide particles is 0.5%-1%, the mass fraction of the carbon black is 0.1%-0.5%, and the rest is water; ②Preparing a white slurry for a foaming coating: taking polyacrylate slurry, titanium dioxide slurry, ammonium stearate emulsion and water, mixing them evenly to obtain a mixed white slurry, adjusting the pH of the mixed slurry to 8-9, and obtaining a white slurry for a foaming coating; in the mixed white slurry, the mass fraction of the polyacrylate slurry is 70%-80%, the mass fraction of the titanium dioxide slurry is 10%-15%, the mass fraction of the ammonium stearate emulsion is 5%-10%, and the mass fraction of water is 0-10%; ③ Preparation of shading fabric: foam the slurries obtained in steps ① and ② respectively, with a foaming ratio of 1:3 to 1:4, and then apply the foamed slurries on the surface of the fabric in the order of white slurry, black slurry and white slurry. After each application, bake at 150 to 180° C. for 2 to 5 minutes to finally obtain shading fabric; the weight gain of shading fabric is in the range of 20 to 40 g / m 2 .

10. Use of the flame-retardant sunshade foam coating fabric according to any one of claims 1 to 9 in the field of flame-retardant fabrics or sunshade.

Citation Information

Patent Citations

  • A method for preparing a stable flame retardant

    CN107629250B

  • Preparation method of textile flame retardant

    CN112663340A

Cited By

  • Preparation method of foam-stabilizing particles and high-stable foaming coating slurry

    CN120250359B